Analisis dan Desain Model UI/UX untuk Pengguna Manusia Lanjut Usia dalam Transformasi Bisnis Pertanian Digital - Herdin Yohnes Madawara; Irwan Sembiring; Budhi Kristianto (JURNAL INFOTEL, 2024)
Digital agriculture faces challenges, namely in integrating Elderly People (SENIORS) in digital transformation. The purpose of the study is to analyze and design UI/UX models according to user needs, expectations, and challenges. The method used is the Design Thinking approach which begins with literature study, then interviews are conducted to identify problems faced by users, and analyze the need to determine problem priorities. UI/UX prototypes are carried out to design solutions that suit user needs, and evaluations are carried out to collect user feedback. The data is assessed through the System Usability Scale (SUS) approach to appraise the designed user interface (UI). The evaluation results showed a "good" rating based on the SUS category, with a final average score of 74,391, so that the solutions designed meet usability standards for SENIORS users in the context of digital agriculture. Thus, the research carried out contributes to increasing the effectiveness and adoption of SENIORS in digital agriculture, as well as by designing user-friendly UI/UX models, making an important step towards inclusive and sustainable digital agriculture.